An examination of plus-size people’s clothes purchasing preferences in e-commerce - Aulia, Muhammad Rizki; Dellyana, Dina (Journal of Innovation, Business and Entrepreneurship, 2019)
Globalization has had a major impact on digital business in the past 20 years,the ease of online transactions is also felt by Indonesians affected by obesity, which reached 19.6% in 2013, this of course has an impact also on the people who categorized as Plus-size. Based on the Asia-Pacific standard for obesity, a person is said to be plus size when the waist circumference exceeds 90 inches for men and 80 inches for women.Clothing products are considered high risk items, therefore various companies are willing to promote their products to facilitate customers. This study aims to analyze of the preferences of plus size people in the transaction of clothing through e-commerce, a sample of 122 people was used in this study to measure dominant preferences in each of the factors, further researchers use quantitative analysis to validate data to respondents. The method used in this study is the Analytic Hierarchy Process (AHP) because the researcher wants to know what factors most influence their preferences in shopping online using ExpertChoiceTM software. Based on the results of the study, researchers want to provide insight in the form of factors that influence consumer preferences.Keywords: AHP, customer preference, e-commerce, pairwise comparison, plus-size people